Sistem Penerapan Artificial Intelligence Dalam Akuntansi: Indonesia - Muh. Fathir Maulid Yusuf, Ilham Akbar Garusu, Dian Mayafaty Rauf (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
This research analyzes the impact of implementing Artificial Intelligence (AI) in the field of accounting, focusing on process efficiency, data accuracy, and strategic decision-making. Involving several companies as case studies, the research results indicate that the implementation of AI significantly enhances efficiency through the automation of routine tasks, reducing the time spent on transaction recording, and enabling accounting staff to focus on more in-depth analysis. Additionally, AI systems demonstrate their ability to improve the accuracy of financial information by identifying and reducing human errors in recording. The adoption of AI also provides deeper data analysis, allowing for the early detection of significant financial patterns and supporting strategic decision-making by providing more informed insights. However, this research highlights several challenges, including issues related to data privacy, complex system integration, and ethical concerns regarding the use of AI in accounting. Therefore, companies aiming to transition to AI technology need to prepare the necessary capacities, involve staff with higher technical understanding, and address potential ethical issues. In conclusion, the implementation of AI in accounting brings about positive changes by enhancing efficiency, accuracy, and supporting decision-making. Nevertheless, the emerging challenges require serious attention to ensure that AI implementation can provide maximum benefits in the accounting environment. Keywords: Artificial Intelligence, Accounting